Entry and incumbent innovation - Philipp Weinschenk (Max Planck Institute for Research on Collective Goods, 2010)
We explore how the threat of entry influences the innovation activity of an incumbent. We show that the incumbent's investment is hump-shaped in the entry threat. When the entry threat is small and increases, the incumbent invests more to deter entry, or to make it unlikely. This is due to the entry deterrence effect. However, when the threat becomes huge, entry can no longer profitably be deterred or made unlikely and the investment becomes small. Then the Schumpeterian effect dominates. These results turn out to be very robust.
Keywords: 330; Innovationswettbewerb; Potenzieller Wettbewerb; Markteintritt; Investition; Theorie